Problematic Situation Analysis of the Stages of Human Resources Management by Applying the Principles of Good Governance in Private University at LLDikti Region III Jakarta - Jadidah, Muasisah; Suratno, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The study aims to analyze the problematic situation of the stages of human resource management in private tertiary institutions by applying the principles of good governance and to know the factors that influence the application of the principles of good governance in human resource management. There has been a lot of research on human resource management, however, problematic research analysis of human resource management situations that is by the principles of good governance to maximize the role of institutions as Good University Governance does not yet exist. The benefits of research are information on the application and stages of good governance in the management of human resources in higher education to improve and develop the principles of good governance in achieving the role of institutions as Good Unversity Governances. In this study, the authors used a qualitative methodology, data collection by observation, in-depth interviews, documentary studies, and Focus Group Discussion (FGD). The results of the research were recommendations in the management of human resources by applying the principles of good governance.